PEMBERDAYAAN MASYARAKAT MENGHADAPI MEA MELALUI PELATIHAN KETERAMPILAN DI KOTA MAGELANG - Agrissto Pradana; Ari Suryawan; Tabah Subekti (Universitas Muhammadiyah Surakarta, 2017)
A preliminary observation revealed that a number of people living near Mount Hill considered to start their business but they were lack of money and skills. This community service was conducted through a training purposed for improving their knowledge about enterpreneurship, motivation and skills on resin craft making. Conducted in November 27, 2016 in Magersari, Magelang, it was aimed at those living in RW VII. It was devided into two steps, preparation and training activities. The preparation covered the coordination with the stakeholders and participants, and the materials preparation. While the training activity provided the introduction of entrepreneurship, motivation and resin crafting experience. SWOT technique was presented in the entrepreneurship discussion activity. Then the crafts they experienced was made of resin. Based on the result, it can be concluded that the training gave them better understanding about entrepreneurship. Besides, they were finally able to create resin crafts. Follow-up was so needed to develop their skills that could be a souvenier business in Mount Tidar.